What’s Cooking? – Cognitive Training of Executive Function in the Elderly - Wang, Man-Ying; Chang, Chien-Yu; Su, Shou-Yi (Frontiers in Psychology, 2011)
Executive function involves the efficient and adaptive engagement of the control processes of updating, shifting and inhibition (Miyake, 2000) to guide behavior toward a goal. It is associated with decrements in many other cognitive functions due to aging (Raz, 2000; West, 1996) with itself particularly vulnerable to the effect of aging (Treitz, Heyder, & Daum, 2007). Cognitive training in the form of structural experience with executive coordination demands exhibited effective enhancement in the elderly (Hertzog, Kramer, Wilson, & Ulman, 2009). The current study was thus aimed at the development and evaluation of a training regime for executive function in the elderly. The breakfast cooking task of Craik and Bialystock (2006) was adapted into a multitasking training task in a session (pre-test vs. post-test) by group (control vs. training). In the training condition, participants constantly switched, updated and planned in order to control the cooking of several foods and concurrently performed a table-setting secondary task. Training gains were exhibited on task related measures. Transfer effect was selectively observed on the letter-number sequencing and digit symbol coding test. The cooking training produced short term increase in the efficiency of executive control processing. These effects were interpreted in terms of the process overlap between the training and the transfer tasks.